PILOT PLANT PENGOLAHAN AIR MINUM DENGAN PROSES BIOFILTRASI DAN ULTRAFILTRASI - Said, Nusa Idaman; Widayat, Wahyu (Center for Environmental Technology, 2008)
Until now, the drinking water companies in Indonesia still use chlorine for disinfection processes. In addition, the chlorine also uses for removal Fe, Mn and ammonia. If the raw water contains high concentration of ammonia, chlorine will react with ammonia form chloramines which have lower strength of disinfection power. The higher concentration of ammonia in raw water caused the higher consumption of chlorine. The reaction of chlorine with certain organic compounds as humic substances will to produce chloro-organo compounds like chlorophenols which become serious problems to day because trihalomethane and also chlorophenols compounds are carcinogenic substances.To overcome the problems one of alternative is using the combination of biofiltration and ultrafiltration to process the drinking water. Biofltrations process is treatment of raw water biologically using fixed bed biofilter reactor witch filled with honeycomb plastic supporting media for removal Fe, Mn, ammonia detergent, and also organic substances. Ultrafiltration (UF) is filtration process using hollow fiber membranes that have effective pore sizes of 0.1 Ã¢â‚¬â€œ 0.01 Ã‚Âµm. The ultrafiltration units are capable of separating some large molecular weight dissolved organics, colloids, macromolecules and suspended solids from raw water. The ultrafiltration process is designed to remove colloidalized particles in the range from 0.1-0.01Ã‚Âµm.By combining the biofiltration and ultrafiltration processes, hence will be got technological alternative of drinking water process which capable to degrade an organic matter, ammonia, detergent and can remove the colloidal or suspended matter effectively without chemicals instead of conventional process.Ã‚Â Kata Kunci : Pengolahan Air Minum, Biofiltrasi, Membran, Ultrafiltrasi, Pilot Plant